Reduced cortical excitability in depression. Impaired post-exercise motor facilitation with transcranial magnetic stimulation. - Shajahan, P; Glabus, M; Gooding, P; Shah, P; Ebmeier, K (1999)
BACKGROUND: In healthy controls, preactivation of muscles by exercise results in enhanced motor-evoked potential (MEP) responses to transcranial magnetic stimulation (TMS). AIMS: We tested the hypothesis that medicated, depressed patients would show reduced post-exercise MEP facilitation compared with controls. METHOD: Ten patients with DSM-IV depression (two male, eight female) and ten controls (three male, seven female) participated. MEPs were elicited at rest, then after exercising the contralateral abductor pollicis brevis muscle, using TMS of the primary motor cortex. RESULTS: The mean MEP amplitude recorded after exercise (expressed as a percentage of baseline) was 210% in controls and 130% in patients. There was a significant difference in post-exercise MEP between patients and controls (P = 0.03). CONCLUSIONS: Post-exercise MEP facilitation was demonstrated in controls but not in patients. This supports the hypothesis that the modulation of cortical excitability may be impaired in depression.